Intervensi Terapi Komplementer Nyeri Dismenore Pada Remaja Putri Menggunakan VOSviewer - Indria, Gita Ayu (Jurnal Ayurveda Medistra, 2024)
Complementary therapy to overcome dysmenorrhea pain in adolescents is one of the alternatives to health services, especially adolescent health. Dysmenorrhea pain experienced by adolescents during the menstrual period can interfere with adolescent activities and increase the number of adolescent pain which will affect the health of adolescents. The researcher aims to find out the bibliometric analysis in the study of the use of complementary therapy to manage dysmenorrhea pain in adolescent girls. Data collection using the Harzing's Publish or Peris application with the keyword "Complementary Therapy, Dysmenorrhea Pain Massage, Adolescents" in articles for the period 2019 – 2024 after the data was processed with VOSviewer software. The results of three clusters were obtained, namely the red cluster consisting of lavender aromatherapy, counterpressur massage, dysmenorrhea pain, adolescent girls, and complementary therapy. The second cluster is green consisting of acupressure, dysmenorrhea, endorphin massage, adolescents. The third cluster is blue, namely rose aromatherapy, primary dysmenorrhea, massage efflurage, menstrual pain. Massage efflurage is a complementary therapeutic intervention in dysmenorrhea pain that is most often used in research.